ANXIETY ENCODED IN PERSONALITY: MUSICAL PERSONALITY AND THE ANXIETY OF THE MUSICIANS - BANDI, Szabolcs; NAGY, Sándor Imre; VAS, Bence (Studia Universitatis Babes-Bolyai Musica, 2017)
The aim of the study is to provide a brief introduction to the cultural history of the personality psychological based findings of the musical profession. As we can see, in the different historical areas very wide variety of views appeared, until in the second half of 20th century music psychology, as evidence based empirical discipline formalised these naive theories. The most important findings were that the personality structure of musicians is fundamentally differs from the normal population (1); and the constantly reported higher level of anxiety-related traits in the case of musicians (2). The latter finding highlights the importance of teaching different techniques of mental hygienical interventions during the music teacher training courses in order to avoid psychopathological symptomatizing and the short-term burn-out of career entrant teachers.